2019
DOI: 10.5582/ddt.2019.01009
|View full text |Cite
|
Sign up to set email alerts
|

Impact of non-selective beta blockers on portal hypertension and hepatic elasticity in hepatitis C virus-related liver cirrhosis

Abstract: Portal hypertension and its complications are the leading causes of morbidity and mortality in patients with liver cirrhosis. Noninvasive assessment of liver stiffness had been an effective tool for assessment of fibrosis progression in chronic liver disease. It was intended to assess liver stiffness measurement (LSM), portal vein diameter (PVD), splenic bipolar diameter (SD), and the platelet count/spleen diameter (PC/SD) ratio in patients who test positive for the hepatitis C virus (HCV) and to study the imp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 17 publications
(20 reference statements)
0
4
0
1
Order By: Relevance
“…show that the effects of NSBB or combined alpha-betablockers on LS are heterogeneous-sometimes decreasing, other times increasing, LS. [11][12][13][14][15]28 The ultrasound-based study by Choi et al found similar both increasing and decreasing LS after NSBB, but they showed a strong correlation between changes in LS and changes in HVPG.…”
Section: The Effect Of Nsbb On Ls and Ssmentioning
confidence: 94%
See 2 more Smart Citations
“…show that the effects of NSBB or combined alpha-betablockers on LS are heterogeneous-sometimes decreasing, other times increasing, LS. [11][12][13][14][15]28 The ultrasound-based study by Choi et al found similar both increasing and decreasing LS after NSBB, but they showed a strong correlation between changes in LS and changes in HVPG.…”
Section: The Effect Of Nsbb On Ls and Ssmentioning
confidence: 94%
“…Spleen stiffness optimal cut-off was an increase in spleen stiffness of 0.3 kPa after NSBB, and the area under the ROC curve was 0.53 (CI 0.32-0.75) (B), with a specificity of 1.00 and a sensitivity 0.19 show that the effects of NSBB or combined alpha-betablockers on LS are heterogeneous-sometimes decreasing, other times increasing, LS. [11][12][13][14][15]28 The ultrasound-based study by Choi et al found similar both increasing and decreasing LS after NSBB, but they showed a strong correlation between changes in LS and changes in HVPG.…”
Section: The Effect Of Nsbb On Ls and Ssmentioning
confidence: 94%
See 1 more Smart Citation
“…As far as detecting changes in portal pressure after various therapies, LSM was unreliable in evaluating the effect of NSBB, and NSBB could not significantly change the stiffness of the liver ( 122 ). While hemodynamic factors such as SSM and the portal vein diameter showed a correlation with the changed PH ( 104 , 108 , 133 ). In the situation of antiviral therapy, SSM could also reflect changes in portal hypertension ( 134 ).…”
Section: Discussionmentioning
confidence: 95%
“…Non selektif beta blocker seperti propranolol dan nadolol, pada pasien sirosis digunakan untuk menurunkan hipertensi portal dan mencegah perdarahan varises (Angeli et al, 2018). Propranolol merupakan non selektif beta-blocker yang paling banyak digunakan pada pasien sirosis (Zaghloul et al, 2019). Propranolol pada pasien sirosis hepatik terbukti efektif dalam menurunkan hipertensi portal dan mencegah terjadinya perdarahan varises serta mengurangi resiko komplikasi lain (Angeli et al, 2018).…”
Section: Hasilunclassified